Transcatheter arterial embolization for massive hemobilia with N-butyl cyanoacrylate (NBCA) Glubran 2. (March 2022) - Shi, Yadong; Chen, Liang; Zhao, Boxiang; Huang, Hao; Lu, Zhaoxuan; Su, Haobo
Background: Massive hemobilia is a life-threatening condition and therapeutic challenge. Few studies have demonstrated the use of N-butyl cyanoacrylate (NBCA) for massive hemobilia. Purpose: To investigate the efficacy and safety of transcatheter arterial embolization (TAE) using NBCA Glubran 2 for massive hemobilia. Material and Methods: Between January 2012 and December 2019, the data of 26 patients (mean age 63.4 ± 12.6 years) with massive hemobilia were retrospectively evaluated for TAE using NBCA. The patients' baseline characteristics, severities of hemobilia, and imaging findings were collected. Emergent TAE was performed using 1:2–1:4 mixtures of NBCA and ethiodized oil. Technical success, clinical success, procedure-related complications, and follow-up outcomes were assessed. Results: Pre-procedure arteriography demonstrated injuries to the right hepatic artery (n = 24) and cystic artery (n = 2). Initial coil embolization distal to the lesions was required in 5 (19.2%) patients to control high blood flow and prevent end-organ damage. After a mean treatment time of 11.2 ± 5.3 min, technical success was achieved in 100% of the patients without non-target embolization and catheter adhesion. Clinical success was achieved in 25 (96.2%) patients. Major complications were noted in 1 (3.8%) patient with gallbladder necrosis. During a median follow-up time of 16.5 months (range 3–24 months), two patients died due to carcinomas, whereas none of the patients experienced recurrent hemobilia, embolic material migration, or post-embolization complications. Conclusion: NBCA embolization for massive hemobilia is associated with rapid and effective hemostasis, as well as few major complications. This treatment modality may be a promising alternative to coil embolization.